2012
DOI: 10.1084/jem.20111580
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Wnt/β-catenin signaling inhibits glioma angiogenesis and normalizes tumor blood vessels by inducing PDGF-B expression

Abstract: Wnt modulates glioma vascularization by regulating PDGF-B expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
116
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(134 citation statements)
references
References 63 publications
(94 reference statements)
13
116
2
Order By: Relevance
“…S5). Consistent with a model in which activation of the Wnt/b-catenin/NOTCH signaling pathway in tumor endothelia leads to VN, 43 we observed that reduced mean vascular density and improved pericyte-VEC interaction in the TME are biologic correlates associated with therapeutic vaccination against DLK1/DLK2 in tumor-bearing mice.…”
Section: Discussionsupporting
confidence: 89%
“…S5). Consistent with a model in which activation of the Wnt/b-catenin/NOTCH signaling pathway in tumor endothelia leads to VN, 43 we observed that reduced mean vascular density and improved pericyte-VEC interaction in the TME are biologic correlates associated with therapeutic vaccination against DLK1/DLK2 in tumor-bearing mice.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, as presented in Fig. 2B, the mRNA expression level of the aforementioned molecules was presented as quartiles, which revealed that the median mRNA expression levels of Wnt3a, Wnt5a, FZD2, 6 and 7 were increased relative to the other molecules, which was similar to the results from the R2 platform and those of TCGA database (13). However, significant changes were not detected in the mRNA expression levels of β-catenin and its degradation complex, including APC, GSK 3β, AXIN1, cyclin D1 or AXIN2, in the glioma samples (Fig.…”
Section: Resultssupporting
confidence: 80%
“…Wnt5a, one of the most highly investigated non-canonical Wnt molecules, has been revealed to be upregulated in multiple types of cancer, including melanoma (31), breast carcinoma (32), pancreatic cancer (33), prostate carcinoma (34) and human glioblastoma (13). Notably, Wnt5a is the most upregulated Wnt member in glioma cells and tissues, which promotes cell proliferation, migration and tumorigenesis both in vitro and in vivo (15,35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Canonical Wnt signaling plays an established role during early steps of embryonic stem cell to EC differentiation (Wang et al, 2006), remodeling of the embryonic vessels (Cattelino et al, 2003;Corada et al, 2010) and establishment of organ-specific vasculatures (Liebner et al, 2008;Stenman et al, 2008;Daneman et al, 2009). Furthermore, canonical Wnt signaling has been described to interfere with vessel regression by stimulating EC proliferation during postnatal retinal angiogenesis (Phng et al, 2009) and to promote pericyte recruitment, thereby inducing tumor vessel normalization (Reis et al, 2012). By contrast, evidence for noncanonical Wnt signaling during angiogenesis is only beginning to emerge (Masckauchan et al, 2006;Cirone et al, 2008;Descamps et al, 2012).…”
Section: Introductionmentioning
confidence: 99%